Leveraging item-level accuracy and reaction time to address ceiling effects in the measurement of inhibitory control in preschool-aged children - Willoughby, Michael T.; Camerota, Marie; King, Katherine Merseth; Nduku, Tabitha; Piper, Benjamin (Frontiers in Psychology, 2023)
Preschool-aged children’s performance on inhibitory control tasks is typically represented by the overall accuracy of their item responses (e.g., mean proportion correct). However, in settings where children vary widely in age or ability level, inhibitory control tasks are susceptible to ceiling effects, which undermine measurement precision. We have previously demonstrated a general approach for scoring inhibitory control tasks that combines item-level accuracy and reaction-time information to minimize ceiling effects. Here, we extend that approach by incorporating additional item-level reaction time data from an adjunct (simple reaction time) task. We contrast three approaches for scoring inhibitory control tasks, two of which rely exclusively on item accuracy information and a third which also considers item reaction time information. We demonstrate the impacts of these different approaches to scoring with two inhibitory control tasks that were included in a recent evaluation of the Red Light, Purple Light intervention in preprimary classrooms in Nairobi County, Kenya. We limited our study to children who met inclusion criteria at pre-test (N = 418; 51% male; mean age = 4.8 years) or post-test (N = 386; 51% male; mean age = 4.8 years). Children’s performance on individual inhibitory control tasks was strongly correlated regardless of the scoring approach (rs = 0.73–0.97 across two tasks). However, the combined accuracy and reaction time scores eliminated ceiling effects that were common when only accuracy information was used. The combined accuracy and reaction time models also distinguished item-level RT into inhibitory control and processing speed components, which are distinct constructs. Results are discussed with respect to the challenges and nuances of the estimation and interpretation of inhibitory control task scores with children of varied ages and ability levels.